Cognitive load affects postural control in children - Schmid, Maurizio; Conforto, Silvia; Lopez, Luisa; D’Alessio, Tommaso (Experimental brain research, 2007)
Inferring relations between cognitive processes and postural control is a relatively topical challenge in developmental neurology. This study investigated the effect of a concurrent cognitive task on postural control in a sample of 50 nine-year-old children. Each subject completed two balance trials of 60 s, one with a concurrent cognitive task (cognitive load) and another with no cognitive load. The concurrent cognitive task consisted of mentally counting backwards in steps of 2. Twelve posturographic parameters (PPs) were extracted from the centre of pressure (CoP) trajectory obtained through a load cell force plate. Analysis of variance revealed significant differences in the majority of the extracted PPs. CoP was found to travel faster, farther, and with substantially different features demonstrating an overall broadening of the spectrum in the frequency domain. Nonlinear stability factors revealed significant differences when exposed to a concurrent cognitive task, showing an increase of instability in the intervention rate of the postural control system. By grouping children through selected items from Teachers Ratings and PANESS assessment, specific significant differences were also found both in time and frequency domain PPs, thus confirming the hypothesis of an interaction between cognitive processes (and their development), and postural control.